(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the effect of pre-infarct angina on post-MI left ventricular function in patients with acute STEMI. Study Design: Comparative study Place and Duration of Study: This study was conducted at the Department of Cardiology, Bahawal Victoria Hospital, Bahawalpur, from May 2018 to October 2018. Materials and Methods: Two hundred and thirty patients admitted to the Cardiology Department with the diagnosis of acute STMI who subsequently received thrombolytic therapy were enrolled in the study. The data were recorded on a performa which included demographic characteristics, history of risk factors for coronary artery disease, time from symptom onset to presentation; and the presence or absence of pre-infarction angina. All the enrolled patients underwent 2-dimensional echocardiography to assess left ventricular ejection fraction before discharge. The data was entered and analyzed with SPSS version 20. The patients were divided into two groups depending upon the presence or absence of pre-infarct angina. The categorical variables were compared between the two groups with chi-square test. The left ventricular ejection fraction was compared between the two groups with two-tailed t-test. A p value of <0.05 was considered to be significant. Results: Pre-infarct angina was present in 58.7 % of the patients. There were no significant differences with regards to baseline characteristics in patients who experienced pre-infarct angina as compared to those who didn’t have preinfarct angina. Post-MI ejection fraction was significantly higher in patients who experienced pre-infarct angina. Conclusion: The patients with pre-infarct angina have better post-MI left ventricular ejection fraction.